Reliability of distribution networks with microgrids - Paulo Moisés Costa (2005)
The emergence of micro-generation as a technically sound alternative has lead, in recent times, to the concept of microgrid, a network of LV consumers and producers able to export electric energy in some circumstances and also to work in a isolated way in emergency situations. Research work about the organization of microgrids, control devices, functionalities and other technical and economic aspects is presently being carried out, in order to establish a consistent technical framework to support the concept. Among other aspects, the effect of microgrids in the reliability of the distribution network has been pointed out as an important advantage, due to the ability of isolated operation in emergency situations. In order to address this topic, the present paper identifies the situations where the existence of a microgrid may reduce the interruption rate and time and thus improve the reliability indices of the distribution network. The relevant expressions necessary to quantify the reliability are also presented. An illustrative example is included, where the global influence of the microgrid in reliability is commented.